Trading Digitalization: Legal Awareness in the Disruption Era - Anindya Aryu Inayati; Noorma Fitriana M. Zain; Nur Afifah; Eko Nur Cahyo (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2023)
The digitalization of trading is developing rapidly, but legal awareness has not been well developed. Although digital trading is fairly new in the world of economics in this country, it has been able to attract the attention of many people, especially business people, to become traders. Digital trading refers to trading activities using applications on smartphones or trading software commonly called trading robots. But unfortunately, the rise of digital trading activities is not accompanied by regulations that guarantee the safety of novice traders. Together with the inhabitants of Pekalongan's ignorance of the rules and laws pertaining to trading activities on the capital market. The purpose of this study is to examine the factors that prevent Pekalongan citizens from being aware of the legal implications of digital trading and know the implications of the lack of legal awareness of the people of Pekalongan regarding digital trading. This study employs both statutory and conceptual approaches and is grounded in empirical legal research. Techniques for descriptive qualitative data analysis. The population of Pekalongan served as the sample for this study, which used a random sampling technique. The findings of this study indicate that low literacy rates and a lack of interest in commodities trade are the main causes of the lack of legal awareness among Pekalongan residents (trading). The consequences of the people of Pekalongan's lack of legal awareness with regard to digital trading are: 1) They lack legal protection in transactions involving digital trading, and 2) They are vulnerable to fraud and losses in such transactions.